A Scholar's Conscience : Selected Writings of J. Saunders Redding, 1942-1977 - Redding, J. Saunders (Jay Saunders), 1906-1988 (Book collections on Project MUSE., 1992)
J. Saunders Redding (1906-1988) was often and justifiably called ""the dean of African American scholars."" As professor and man of letters, he wrote about African American literature and culture in vivid and scholarly prose. And of all the writers of his generation, he best represented, and came closest to explaining, the hopes and conflicts of American democracy in a multiracial society. Yet his perceptions and writings were never limited to race, nationality, academia, or one literary genre. In this first published anthology drawn from Redding's books, essays, and speeches, Faith Berry has c.